Regional Development Of Medan City - Feby Milanie (Yayasan Multidimensi Kreatif, 2023)
This study aims to analyze the influence of biogeophysical aspects, economic aspects, location aspects, socio-cultural aspects, institutional aspects, and environmental aspects on water supply and clean water demand in Medan City.The data used in the study are secondary and primary data obtained from relevant agencies and communities in Medan City. Secondary data were obtained from 1990 - 2012, and primary data were obtained from 30 respondents. The analysis model used is the Structural Equation Model (SEM) Lisrel PLS (Partial Least Square), the decision-making model or Analysis Hierarchy Process (AHP) model, and the strategic planning model or Strengths Weaknesses Opportunities Threats (SWOT) model. The results showed that: biogeophysical aspects have a positive and significant effect on water supply and clean water demand